Actividades lúdicas y su influencia en el desarrollo de la expresión oral en el área de lengua y literatura en la educación híbrida en los niños del quinto año de educación básica paralelo “b” de la escuela de educación básica “Luis Aurelio González” de la ciudad de Guaranda en el año lectivo 2021-2022. - Cajilema Caiza, Diego Vinicio (2022)
In the investigative work, it analyzes two variables, playful activities and development of oral expression, it aims to determine playful strategies that allow the development of oral expression in the students of the Fifth General Basic Education of the Luis Aurelio González Educational Unit of the city of Guaranda Bolivar province. Using the methodology under a qualitative approach, that is, it will allow to obtain a deep analysis of the reality studied and at the same time obtain points of view of the subjects under investigation based on the meaning that this will establish through data collected in the observation sheet. , as well as the survey to show results. The research will be developed through the exploratory design, considering the need to explore and investigate to achieve the objectives set, with a descriptive and bibliographical research; with data collection techniques and instruments such as the interview with the teacher, an observation sheet addressed to the students, conducting an analysis of the behavior of the fifth students, and a survey of parents, which were very useful for the collection and analysis of the necessary information. . By developing a guide of playful and dynamic activities that allow strengthening the development of oral expression. Concluding that specifically in the development of oral expression, playful activities and games, it will precisely develop the skills, abilities to systematize playful activities and the influence on the development of oral expression. Keywords: Recreational activities, oral expression, hybrid education, strategies.